2007
DOI: 10.1111/j.1365-2966.2007.12025.x
|View full text |Cite
|
Sign up to set email alerts
|

Some estimates of the source counts at Planck Surveyor frequencies, using the 9C survey at 15 GHz

Abstract: We have used multifrequency follow‐up observations of a sample of extragalactic sources from the 9C survey at 15 GHz to make deductions about the expected source population at higher radio frequencies, such as those in the lower frequency bands of the Planck Surveyor satellite. In particular, we have made empirical estimates of the source counts at 22, 30, 43 and 70 GHz and compared these with both known data and current theoretical predictions. We have also made an estimate of the count at the Atacama Large M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 19 publications
(28 reference statements)
9
45
4
Order By: Relevance
“…In particular, a clear steepening (or a bending down) at mm wavelengths is theoretically expected (Kellermann 1966;Blandford & Königl 1979). This steepening has been already observed in some well known blazars (Clegg et al 1983) and has also been statistically suggested by recent analyses of different ERS samples at ν > 30 GHz (see, e.g., Waldram et al 2007;Gonzalez-Nuevo et al 2008).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In particular, a clear steepening (or a bending down) at mm wavelengths is theoretically expected (Kellermann 1966;Blandford & Königl 1979). This steepening has been already observed in some well known blazars (Clegg et al 1983) and has also been statistically suggested by recent analyses of different ERS samples at ν > 30 GHz (see, e.g., Waldram et al 2007;Gonzalez-Nuevo et al 2008).…”
Section: Introductionmentioning
confidence: 76%
“…At frequencies ν > 20 GHz a further spectral steepening is still possible: a recent indication in this sense is coming from the follow-up of 9C sources (see Waldram et al 2007). …”
Section: High-frequency Steepening Of Steep-spectrum Sourcesmentioning
confidence: 99%
“…(a) [HB89] 0906+015, (b) PKS 0907+022. (Waldram et al 2007;Sadler et al 2008). Vieira et al (2009) find that their highest significance 150 GHz selected radio sources are consistent with flat spectral behavior (or α 0.1) between 5 GHz and 150 GHz but a possible steepening between 150 and 220 GHz.…”
Section: Introductionmentioning
confidence: 94%
“…2): a sharp decrease of the slope at faint flux densities (S ν < ∼ 1 Jy at 30 GHz) signals the onset of incompleteness. Based on the ATCA 20 GHz counts Murphy et al 2010), we expect that the slope of the counts remains approximately constant over the limited flux density range covered by Kovac et al 2002) and at 33 GHz from the VSA data (grey box; Cleary et al 2005); the counts from the PACO (grey diamonds; Bonavera et al 2011) and the WMAP 5-yr surveys (grey squares; Massardi et al 2009), at the closest frequencies, and the counts estimated by Waldram et al (2007) (grey dashed line), exploiting multi-frequency follow-up observations of the 15 GHz 9C sources. The vertical dashed magenta line in the upper panel indicates the flux density completeness limit, 1.0 Jy, estimated for our primary sample Sect.…”
Section: Completeness and Uniformity Testsmentioning
confidence: 99%